Voting Behavior of People Towards Different Political Parties in District Faisalabad, Pakistan - Shawar, Durre E.; Asim, Muhammad (Richtmann Publishing, 2012)
Voting is the main form of political participation in democratic societies and the study of voting behavior is a highlyspecialized sub-field in political and social science. The study was concerned with the reasons why people vote the way they do.The main objectives of the present study were to find out the factors which affect the voting behavior & to explore the factors thatconstitute political affiliation in District Faisalabad. A sample of 160 household respondents was selected systematically fromDistrict Faisalabad through multistage sampling technique. Specifically explored through this study the relationship of votingbehavior with education, internal changes in the party, voter’s satisfaction and biradrism are those factors that had strong effecton voting decisions. More than fifty percent (55%) of the respondents vote for the candidate not for the party and (53.1%) of thevoters change their behavior due to the internal changes in the party. The value of Chi-Square and Gamma showed a significantand strong association between voter satisfaction with particular political party, favour of biradrism and internal change in theparty are strongly associated with voter's behavior.